EFFECT OF SERVICE QUALITY, CUSTOMER TRUST AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY AT PT LAUTAN INDOMAS UTAMA MEDAN - Andrianto Andrianto; Nurmaidah Ginting; Calvin Calvin; Vina Fransiska; Vincent Vincent (SEAN Institute, 2023)
The results show that the adjusted r square value is 0.302 which means that 30.2% of customer loyalty demand is jointly influenced by the variables described in the model. While the rest is influenced by factors outside the model. Partially, service quality variable has a positive and significant effect, trust variable has a positive and significant effect, customer satisfaction variable has a positive and significant effect. Simultaneous, service quality, trust and customer satisfaction have a positive and significant effect.